Estudo do nivel piezometrico por analise geoestatistica - Sturaro, J. R.; Landim, P. M B (My University, 1988)
160 groundwater bores in the Ribeirao Preto region were used to study the behaviour of the piezometric surface of the Botucatu Formation aquifer by geostatistical methodology. The semi-variogram showed the following results: nugget = 50 m2; sill = 450 m2 and range = 4.5 km. The piezometric surface, obtained by punctual kriging in a 100 x 100 knot grid, revealed two lowered zones: one in a southwest to north-northeastern trend, indicating the groundwater flow north toward the Rio Pardo; and the other in the central part due to the high concentration of holes in the urban region of Ribeirao Preto city. -from English summary
Piezometric surface study by geostatistics methodology
Keywords: geostatistical method; groundwater flow; piezometric surface; Brazil, Rio Pardo